The Comparison of Hardiness and Coping Styles with Psychological Stress in Addicted and Normal People - Rahim Molazadeh, E; Mousa Kafy; Eraj Salehy (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The purpose of this study was to compare the hardiness and coping styles with stress in addicted and normal people in the city of Rasht. Method: The method of this study was causal comparative research. In sampling one hundred addicts were selected by multistage cluster sampling and one hundred normal ones selected by available sampling, then the Kobasa personal views survey and Moos and Billings coping styles questionnaires were administered among both groups. The Pearson correlation coefficients, independent samples t-test and regression analysis were used for data analysis. Results: The results showed that there were significant differences between the mean scores of hardiness and emotion focused coping style in addicted and normal people, but there was no significant difference on problem focused coping style. Regression analysis also showed that hardiness can be a significant predictor for emotion focused coping style. Conclusion: The findings of this research show the important role of some of the personality characteristics such as hardiness and coping styles with stress that may correlate with the tendency to addiction and substance abuse in people.